HPV‐Associated Tumor Eradication by Vaccination with Synthetic Short Peptides and Particle‐Forming Liposomes. Issue 11 (19th February 2021) - He, Xuedan; Zhou, Shiqi; Quinn, Breandan; Jahagirdar, Dushyant; Ortega, Joaquin; Abrams, Scott I.; Lovell, Jonathan F.
Abstract: Human papilloma virus (HPV)‐16 is associated with cervical cancers and induces expression of the E6 and E7 oncogenes. Using a murine cell line that expresses these, the genes are sequenced, and six predicted major histocompatibility complex (MHC) class I (MHC‐I) epitopes are identified. A liposomal vaccine adjuvant based on cobalt–porphyrin‐phospholipid (CoPoP) is admixed with synthetic 9‐mer epitopes appended with three histidine residues, resulting in rapid formation of peptide–liposome particles. Immunization with multivalent peptides leads to protection from tumor challenge. Of the peptides screened, only the previously identified E749–57 epitope is functional. The peptide–liposome particles that form upon mixing E7HHH49–57 with CoPoP liposomes are stable in serum and are avidly taken up by immune cells in vitro. Immunization results in robust protection from tumor challenge and re‐challenge. A 100 ng peptide dose protects mice in a therapeutic tumor challenge when admixed with CoPoP liposomes, whereas 200‐fold higher peptide doses are ineffective with the polyinosinic–polycytidylic (poly(I:C)) adjuvant. CoPoP induces a strong infiltrating CD8 + T‐cell response within the tumor microenvironment with an improved functional profile. Vaccine monotherapy using nanogram dosing of the E7HHH49–57 peptide admixed with CoPoP reverses the growth of large established tumors, eradicating subcutaneous tumors upwards of 100 mm 3 . Immunization also eradicates lung tumors in a metastasis model. Abstract : A liposomal vaccine platform that induces spontaneous conversion of peptides into serum‐stable particles is used with a synthetic short peptide derived from the human papilloma virus. Vaccination results in robust protection from tumor challenge and re‐challenge, a strong infiltrating CD8 + T‐cell response within the tumor microenvironment, and eradicates tumors upward of 100 mm 3 and lung metastases.